Effects of light irradiation on the complexes of cadmium and humic acids: The role of thiol groups. (June 2019) - Jia, Yanming; Zhao, Tuokun; Zhao, Nan; Wei, Hang; Zhang, Weihua; Qiu, Rongliang
Abstract: In natural environments, humic substances (HS) play a key role in the control of Cd stability by forming Cd-HS complexes. In this study, we investigated the influence of the photo-irradiation on the Cd levels remaining in Leonardite humic acid (HA) standard solution after chemical precipitation. The kinetic experiment showed that after the irradiation of ultraviolet light, especially UVC, Cd-HA complexes become more stable. The coexisting Cd in the HA solution under light irradiation seemed to enhance the stability of Cd-HA complexes. Both Fourier transform infrared and X-ray photoelectron spectrometric spectra indicated an increase in the thiol amounts in the HA samples treated by light irradiation. Therefore, we developed a fluorescent method to quantify thiol groups in HA with N-(1-pyrenyl) maleimide (NPM). The HA samples were initially spiked with known amounts of glutathione, the reference containing thiol groups, and then was titrated with various amounts of NPM. The measured thiol amounts in the HA treated by UV were found to significantly increase, and the increment was almost equivalent to those of Cd level in HA solution after chemical precipitation. Therefore, it was concluded that the increased thiol groups in HA induced by ultraviolet irradiation resulted in the formation of more stable Cd-HA complexes in solution. Graphical abstract: Image 1 Highlights: The ultraviolet irradiation increases the stability of Cd-humic acid complexes. Comparatively, the UVC always leads to a greater increment in a shorter duration. The enhanced stability of Cd-humic acid can be ascribed to the increased thiol levels. The higher thiol level was quantitatively confirmed by the fluorescence spectroscopy.